Enhanced LEACH for Distributed Clustering in Heterogeneous Wireless Networks (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless networks have recently come into importance because they hold the potential to revolutionize many segments. Since wireless nodes have battery constraints that limits lifetime of wireless network, Energy management plays a vital role in improving network life time in wireless sensor and ad hoc networks.  In Wireless Sensor network, performance of Routing and energy consumption of wireless nodes are determined by distributed clustering algorithm which is used to distribute the energy and load balancing among nodes by promoting an appropriate node as coordinator. In wireless Ad hoc networks, there is no fixed topology and communications between nodes occur through sink node. An efficient energy rich node is to be elected as sink node dynamically in order to coordinate routing. So, this research focuses to compare the present distributed clustering algorithm (LEACH) with EEDCBRP for wireless Ad Hoc and Sensor network.  During this study, LEACH algorithm which is used to select cluster head, shows some drawbacks that need improvements to overcome it as to improve the performance. This proposal uses energy level and distance of node to select cluster head.  In the wireless network, Base station maintains the table to hold the information about energy and location of the wireless nodes. After receiving the information about all sensor nodes, base station performs the clustering process.  Mobile nodes are grouped into the layer based clusters by checking energy and distance.  The improvement is done in cluster head selection procedure. Finally the performance of proposed algorithm is compared with Low Energy adaptive clustering hierarchy. Network Simulator (NS2) is used to simulate and evaluate the performance.  The results of simulation show that Enhanced Distributed Clustering Routing protocol effectively balances energy consumption of wireless node.